(untitled) (Филолошке студије, 2021)
If we understand „Croatian Tales of Long Ago“ not only as a collection of fairy tales, but also as an authentic piece of women’s writing, i.e. as a text that records, embodies and articulates gender specific experience, new venues open for the analysis of this literary masterpiece.. The two tales discussed, „ Stribor’s Forest“ and „Bridesman Sun and Bride Bridekins“, I understand as the two sides of a coin, the two solutions of the same problem. On the surface, the two stories seem to have different plots and different characters, but if we look beyond the manifest content we find the same conflict latent to both tales: the conflict of the two generations of women, the old mother and the daughter in law. Tales talk about subverting and re-establishing female hierarchies, about subjecting to or rebelling against the rule of the matriarch. In both tales, the masculine is marginal, a mere object, while feminine is active; the subject. The female position, differentiated into the heroine and the villain(esse), is in each of the stories studied from the different perspective, i.e. the different character is the subject. „Stribor’s forest“ demonizes the daughter in law and proclaims her power over the male illegal and her sexuality monstrous, while the old mother is raised to the pedestal of the defender of the righteous order of the maternal rule. In contrast, „Bridesman Sun and Bride Bridekins“ casts the rebel in the role of the heroine. Rejecting the maternal choice of a husband, she opposes oppressive maternal rule, described as monstrous, and successfully takes over.